Perceptions of Agriculture by Elementary School and College Students in Mezam Division of North West Cameroon: A Qualitative Analysis - Vitung, Aseh Emmanuel (CV. Literasi Indonesia, 2023)
The study explored the perceptions of primary school pupils, secondary, and high school students in the Mezam Division of the North West Region of Cameroon. Existing literature points to declining youth interest in agriculture grounded on a largely negative perception of the sector, however, there is scant data on youth perception of agriculture in Cameroon. In the face of rising youth unemployment, there is a need to generate relevant data that can inform policies relating to youth entry and participation in the country’s agriculture. Semi-structured questionnaires were used to collect data from 7 primary, secondary, and high schools respectively. The data were analyzed using the thematic approach, leading to the emergence of themes. The findings of the study indicate that pupils and students have largely positive perceptions of agriculture which are however not translated into high aspirations for career development in the sector, suggesting a need for targeted actions at various levels of the educational system. Further research that addresses perceived determinants of youth attraction to agriculture in the country, will contribute to informing youth-specific policy towards agriculture.